Educational technologies as guidance to patients in the postoperative period of mastectomy: integrative review (Research, Society and Development, 2022)
Breast cancer is a type of malignant tumor that most affects women in much of the world, considered an important public health adversity and as part of the treatment, a surgery called mastectomy (partial or total removal of the compromised breast) is recommended. Objective: To search for scientific studies about educational technologies in post-operative care of mastectomy. Method: Integrative literature review of studies taken from the databases of the Virtual Health Library (BVS) with indexers from Medical Literature Analysis (MEDLINE/Pubmed), (LILACS), and from the Nursing Database (BDENF), Literature America and the Caribbean in Health (LILACS). For operationalization, the following Health Sciences Descriptors (DeCS/MeSH) were used: educational technology, postoperative care, mastectomy. Free online studies, originals in Portuguese, English and Spanish were included and theses, dissertations, informative booklets, duplicate studies and other languages were excluded. A time frame was used between the years 2017 to 2022.Results: 07 eligible studies were identified that resulted in 3 categories: educational technologies for patient education, patient self-management through educational technologies, benefits of teaching and learning through technologies for the patient and the nurse. Conclusion: Technologies applied to health have been a facilitator for the implementation of new resources to meet the needs of care, but it was observed that educational technologies are not widespread with regard to surgical patients, especially those who are in post-operative care. mastectomy surgery.